Digital Instructional Leadership for Strengthening Teacher Discipline and Improving Learning Quality: A Qualitative Study at SMA Negeri 5 Palu - Yulisa, Yulisa; Iskandar, Iskandar; Nongtji, Minarni; Juraid, Juraid (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Digital instructional leadership has become increasingly important in supporting evidence-based school management and improving instructional quality. This study aimed to explore how digital instructional leadership was implemented to strengthen teacher discipline and improve learning quality at SMA Negeri 5 Palu. A qualitative descriptive approach was employed involving the principal and teachers as research participants. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings reveal that digital instructional leadership was implemented through four interconnected practices: data-informed teacher monitoring, instructional supervision, continuous professional development, and adaptive leadership in addressing implementation challenges. Attendance records, teaching journals, classroom supervision, and instructional documentation functioned as evidence-based tools supporting leadership decisions, strengthening teacher accountability, and promoting continuous instructional improvement. In addition, In-House Training (IHT), mentoring, and professional feedback enhanced teachers' pedagogical competence and reinforced professional discipline. Despite challenges related to personal circumstances, contextual conditions, and varying levels of professional commitment, the principal successfully integrated monitoring, supervision, coaching, and professional learning into a coherent instructional improvement system. The study concludes that digital instructional leadership strengthens teacher professionalism and contributes to sustainable improvements in learning quality through evidence-informed instructional management.